KESESUAIAN KLASTER INDUSTRI ANYAMAN BAMBU TERHADAP INDIKATOR KEBERLANJUTAN DI DESA WALEN KECAMATAN SIMO KABUPATEN BOYOLALI - Haji, Vicha Ardhea Puspa; Soedwiwahjono, Soedwiwahjono; Hardiana, Ana (ARSITEKTURA, 2017)
Abstract: Five hamlet in Walen Village, there is Pokoh, Wates, Walen, Jeringan and Ngampon are bamboo industry cluster area. This cluster is characterized by the existence of a bamboo forest as a provider of industrial raw materials, the people who have expertise to weave bamboo, bamboo woven activity and presence of a network or cooperation of small industry craftsmen. Industry cluster is absorbing the local workforce so we need to cuntineu in order to trigger the growth of the local economy. The problem in this research is how the level of sustainability of bamboo woven industry cluster in Walen Village to see between the existing conditions with the concept of sustainability of industrial cluster. The purpose of this study is to determine the suitability of Walen Village, Simo, Boyolali with sustainability concept. This study uses deductive research methods with quantitative research. Analysis uses scoring analysis which is based on the normative and suitability to the needs of the community. Conclusions from this research is the suitability of bamboo woven industry cluster Walen Village towards sostainability concept into the category of medium suitability. Normatively, the sustainability factor were classified as  high compatibility towards sustainability indicators are infrastructure, raw materials and capital; were classified as moderate suitability factors are location and labor; and were classified as low suitability are market, technology, partnership and government support. The result of analysis based on suitability to community needs were classified as high suitability is the raw material; were classified as moderate suitability are location, infrastructure, market, capital, labor, technology and partnership; and were classified as low suitability is government support. Keywords: Industry Cluster, Small Industry, Sustainable Development.